Patients with RET D631Y Mutations Most Commonly Present with Pheochromocytoma and not Medullary Thyroid Carcinoma - Elston, M. S.; Meyer-Rochow, G. Y.; Holdaway, I.; Conaglen, J. V. (Hormone and Metabolic Research, 2012)
Multiple endocrine neoplasia type 2a results from an activating germline mutation in the RET proto-oncogene. Carriers of a RET mutation are at risk of medullary thyroid carcinoma, pheochromocytoma, and primary hyperparathyroidism. Most individuals with multiple endocrine neoplasia type 2a eventually develop medullary thyroid carcinoma and as there is a strong genotype-phenotype correlation, guidelines have been established as to the age recommended for prophylactic thyroidectomy. However for rare mutations in the RET proto-oncogene there is insufficient evidence to provide guidance as to the risk of medullary thyroid carcinoma. We present a family with the rare RET mutation, D631Y in which the proband initially presented with a pheochromocytoma, and review the available literature pertaining to this mutation. In 83% of index cases, pheochromocytoma was the presenting feature and only 37% of adult germline mutation carriers have developed medullary thyroid carcinoma, none of whom have been reported to have nodal or metastatic disease. Patients with a D631Y RET mutation typically present with pheochromocytoma and medullary thyroid carcinoma appears to occur with a later onset than reported with other RET mutations. Based on the current literature we recommend performing prophylactic total thyroidectomy by age 12 years for D631Y carriers although this recommendation may need to be reviewed as additional data becomes available.
Keywords: multiple endocrine neoplasia 2A; c-cell carcinoma; hyperparathyroidism; catecholamines